Abdominoparietal remodeling surgery. - Croci, Fabio; Pérez Penco, Ernesto; Gastambide, Carmelo; Terra, Eneas (Cirugía del Uruguay, 1985)
Abdominoparietal remodeling surgery is a form of re• conslructive surgery intended to create a new adequacy in the containing (functioning) condition in serious and extended parí3tal disorder on the basis of a calculated loss of tensional abdominal flexibility, whereby three basic objectives are achieved: to regain continence; readapt visceral condition; and recover support of phrenic centre. This operation requires the use of prosthetic materials, of which, the best is the Marlex (R) mesh. lndications must be very precise: multioperated abdomens with multiple failures, umbilical hernias and giant centroabdominal ventral hernias and the complex pathology of the bilateral inguinal area. Results are excellent.